An educational model for the classification of factors that affect the efficiency of the redevelopment of the environment and the relocation of industrial companies - Lapidus, Azariy (2021)
The purpose of this study was to determine the hierarchy of fundamental factors determining the possibility of relocation of industrial enterprises in order to rationalize urban infrastructure. By analyzing scientific literature and the method of expert assessments, a list of priority factors has been formed that affect the possibility of redeveloping the urban environment and the relocation of an industrial facility. The use of expert assessment and the Likert scale established causal relationships between factors. A model of the hierarchy of factors has been developed using the graph method, based on the results of which a 5-level structure of factors has been established that affect the possibility of redeveloping the urban environment and relocation of an industrial facility. The obtained results can be useful for business structures, as well as government bodies. It seems that a fuller consideration of the following factors will not so much completely protect projects for the redevelopment of industrial zones in Russian cities from choosing the wrong concepts, not payback, low interest from tourists, but rather reduce the likelihood of making completely non-optimal decisions.